Combining protective clothes with human body models for finite element ballistic impact simulations - Matthias Boljen; Marcin Jenerowicz; Steffen Bauer; Elmar Straßburger (Communications in Development and Assembling of Textile Products, 2023)
The ballistic deformation of an ultra-high-molecular-weight (UHMW) polyethylene (PE) composite has been subjected numerically to a multi-layered soft ballistic fabric package modelled upon the body contours of the Global Human Body Models Consortium (GHBMC) human body models M50-P and F05-P. The results of the clothing-body-interaction have been investigated and compared to the behavior of anthropomorphic surrogate models made from ballistic clay. For building the fabric model in donned shape, a single ply of woven fabric material has been converted upon the anthropomorphic body contour by subjecting it to a quasi-deep drawing process. After the fabric deformation, the shaped layer was duplicated 20 times and shifted outwards to build the fabric model, representing a multi-layered soft ballistic fabric package. The results of the ballistic impact simulation show that the response of the human body models (HBMs) is much more compliant than the behavior of the surrogate models. The deformation of the female HBM in terms of penetration depth and diameter of the affected impact region is slightly more severe than the deformation of the male counterpart with respect to identical impact conditions.